PENGATURAN WEWENANG DALAM PENGELOLAAN WILAYAH LAUT - Sherlock H. Lekipiouw (SASI, 2014)
The concept of a sea area becomes of great importance in relation to the effort against the structuring and setting boundaries utilization and management of marine areas to pay attention to the conception of the country which insists on (1) the boundaries of the Homeland ; and (2) the rights contained within it 's own territory . The above concept is consistency of affirmation of the principle and characteristic of the archipelago island nation as stipulated in Article 25A NRI Constitution of 1945 and the right to control the state of the earth and water and natural resources contained therein as intended in Article 33 paragraph (3) Constitution NRI Year 1945 the nature of the provision is to achieve national development goals as defined in the preamble of the Year 1945 NRI in such understanding , the concept of a sea area is related to the philosophical aspects , principles of management and organization authority in the management of marine areas